Isolated Diffuse Mesangial Sclerosis Presenting as Steroid Resistant Nephrotic Syndrome After Infancy - Amisha Undani; Mahaleengam Vijaya kumar; Nageswaran Prahlad; Ekam baram Sudha (Asian Journal of Clinical Pediatrics and Neonatology, 2018)
Diffuse mesangial sclerosis presents with corticosteroid resistant nephrotic syndrome and progressive renal failure usually in the first year of life. With limited resources for genetic mutation studies, kidney biopsy along with clinical findings helps to suspect possible underlying gene mutation. This child with female phenotype and genotype presented with nephrotic features for the first time after one year of age.